The Inflammatory Cytokines in Rheumatoid Arthritis and Their effect in the Progression and Pathogenesis of the Disease - Naser, Saad Ali; Thuwaini, Mahdi M.; Al-Snafi, Ali Esmail (South Eastern European Journal of Public Health, 2024)
Background: Rheumatoid arthritis (RA) is a systemic autoimmune disorder affected the entire body. Aims of the study: Estimation of levels of inflammatory biomarkers in patients with RA and investigation of their impact on the development and severity of the disease. Methodology: This trial is a case-control one involving 44 patients with RA and 44 healthy age matched controls. Blood samples (5 ml) were collected from each participant, anti-CCP, RF, CRP, and ANA levels were measured using a Cobas device, while TNF-α, IL-10, IL-6 and IL-1β, were determined by an ELISA assay. Result: The results showed no significant variations in age, place of residence, and smoking between the RA and control groups, while there were significant variations in BMI, gender, and professional status. The levels of ESR, anti-CCP, RF, ANA, and CRP were significantly elevated in the RA group (P<0.001 for each) than in the control group. The study of cytokine levels also showed significant variations between the two groups, with an increase in TNF-α, IL-6 and IL-1β, and a decrease in IL-10 in the patients. IL-1β was positively correlated with age, IL-6, IL-10, and TNF-α. Conclusions: The results indicate that cytokines levels such as TNF-α, IL-6, IL-1β, and CRP are elevated in RA patients, reflecting elevated inflammatory activity, while levels of IL-10 are decreased, which may contribute to the exacerbation of the disease.